Perceptions of Caregivers about Long-term Care Services in Bangladesh: A Qualitative Descriptive Study - Haque, Akramul; Soonthornchaiya, Rangsiman; Othaganont, Pranom; Chen, Yu-Ju (Pacific Rim International Journal of Nursing Research, 2023)
Long-term care demand for stroke survivors has increased in Bangladesh and other parts of the globe. Family caregivers play a significant role in continuing care for their relatives who are stroke survivors. Still, little is known about their experiences using long-term care services. This study explored the perceptions of Bangladeshi caregivers regarding long-term care use of family members with stroke. A qualitative descriptive study was carried out in the Rangpur division of Bangladesh between February and June 2020. A purposive sampling method was performed to select 15 participants from eligible family caregivers who met the inclusion criteria. Participants were interviewed face-to-face using semi-structured questions and recorded with a digital recording device. The duration of each interview ranged from 60 to 90 minutes. Data were analyzed using content analysis. Four major themes emerged: 1) Understanding of long-term care, 2) The challenges of providing care, 3) Long-term care services as essential support, and 4) Facilitators and barriers to using long-term care services. The findings informed that nursing and multidisciplinary long-term care is needed for stroke survivors in the institutions and at home. The study finding has important implications for the front liners in health sectors, especially for nurses, clinicians, nurse educators, and policymakers to develop specific care units for stroke survivors and train family caregivers to ensure quality long-term care.